Central Integration of Canal and Otolith Signals is Abnormal in Vestibular Migraine - King, Susan; Wang, Joanne; Priesol, Adrian J.; Lewis, Richard F. (Frontiers in Neurology, 2014)
Vestibular migraine (VM), a common cause of vestibular symptoms within the general population, is a disabling and poorly understood form of dizziness. We sought to examine the underlying pathophysiology of VM with three studies which involved central synthesis of canal and otolith cues, and present preliminary results from each of these studies: 1) VM patients appear to have reduced motion perception thresholds when canal and otolith signals are modulated in a coplanar manner during roll tilt; 2) percepts of roll tilt appear to develop more slowly in VM patients than in control groups during a centrifugation paradigm that presents conflicting, orthogonal canal and otolith cues; and 3) eye movement responses appear to be different in VM patients when studied with a post-rotational tilt paradigm, which also presents a canal-otolith conflict, as the shift of the eye’s rotational axis was larger in VM and the relationship between the axis shift and tilt-suppression of the VOR appeared to differ in VM patients relative to control groups. Based on these preliminary perceptual and eye movement results obtained with three different motion paradigms, we present a hypothesis that the integration of canal and otolith signals by the brain differs in VM and that this difference could be cerebellar in origin. We provide several possible mechanisms that could underlie these observations, and speculate that one of more of these mechanisms contributes to the vestibular symptoms and motion intolerance that are characteristic of the VM syndrome.